Pre-school-based behaviour change intervention to increase physical activity levels amongst young children: a feasibility cluster randomised controlled trial - Al-walah, Mosfer A.; Donnelly, Michael; Alhusaini, Adel A.; Heron, Neil (Frontiers in Public Health, 2024)
Background: A significant rise in childhood obesity worldwide over the past three decades highlights the urgent need for early interventions, especially in preschools as key settings for child development. This study aimed to assess the feasibility and fidelity of a randomised controlled trial of "I'm an Active Hero" (IAAH), a theory-and evidence-based multi-component behaviour change intervention targeting physical activity and sedentary behaviour among preschool-aged children.Methods: Two preschools in Taif city, Saudi Arabia were randomly assigned to either the intervention (n=3 classrooms) or the usual curriculum control group (n=3 classrooms). The intervention ran for 10 weeks from February to April 2023 and consisted of teacher-led physical activity and sedentary behaviour sessions in preschools, with an additional interactive home component. Primary outcome measures included intervention fidelity, recruitment rates, attrition rates, and compliance with trial procedures. Secondary outcomes included body mass index (BMI), objectively measured physical activity, and sedentary time via the ActiGraph GT3X accelerometer. Outcomes were measured at baseline and at 10 weeks in both study arms.The preschool intervention component had high fidelity (93.3%), but the home component fidelity was lower (74%). A cluster-level recruitment rate of 12% (13/112 centres) was attained, while the individual-level recruitment rate stood at 36% (52/143 children, mean age of 4.16 years; 23 girls). Attrition was 10%. Compliance varied with 90% for BMI, 71% for accelerometery, and 45% for questionnaires. The intervention group showed small decreases in BMI, slight increases in physical activity, and decreases in sedentary time at follow-up compared to the control group. Parents, facilitators, and assistant teachers considered the intervention to be feasible and beneficial.The IAAH intervention was feasible to implement in Saudi Arabian preschools. Facilitators showed high fidelity in delivering it. However, preliminary data did not demonstrate effectiveness. A more comprehensive evaluation across a broader population is warranted. The intervention could be revised to optimise recruitment, compliance, and fidelity of the home-based component. Successful elements from this pilot should be retained while adaptations to implementation are made to strengthen key areas.